EGFR (Epidermal Growth Factor Receptor) Signaling and the Mitochondria Regulate sFlt-1 (Soluble FMS-Like Tyrosine Kinase-1) Secretion. Issue 3 (March 2019) - Hastie, Roxanne; Brownfoot, Fiona C.; Pritchard, Natasha; Hannan, Natalie J.; Cannon, Ping; Nguyen, Vi; Palmer, Kirsten; Beard, Sally; Tong, Stephen; Kaitu'u-Lino, Tu'uhevaha J.
Abstract : Preeclampsia is a hypertensive disorder of pregnancy characterized by maternal endothelial dysfunction and end-organ damage. The antiangiogenic factor, sFlt-1 (soluble FMS-like tyrosine kinase-1) has been strongly implicated in the pathogenesis of preeclampsia. sFlt-1 is secreted into the maternal circulation where it antagonizes VEGF (vascular endothelial growth factor) and ultimately disrupts vascular homeostasis. However, the upstream mechanisms regulating release of sFlt-1 are poorly characterized. We investigated the roles of key prosurvival pathways, EGFR (epidermal growth factor receptor) signaling, and the mitochondria, in regulating sFlt-1 production. We initially found that the mRNA and protein of EGFR and downstream adaptor molecules were significantly increased in preeclamptic placental tissue relative to normotensive controls. Inhibiting the EGFR signaling cascade using siRNA (small interfering ribonucleic acid) or small molecule inhibitors significantly reduced sFlt-1 release from primary cytotrophoblast (placental cells). Additionally, inhibiting the mitochondrial electron transport chain or activating downstream energy-sensing molecules (AMPK [AMP-activated kinase], SIRT1 [sirtuin 1 ], and PGC1α [PPAR-γ co-activator 1]) also significantly reduced sFlt-1 secretion from cytotrophoblast cells, without affecting EGFR signaling. In vivo, treating pregnant mice with gefitinib (an EGFR inhibitor) or resveratrol (perturbs mitochondrial function) significantly reduced circulating murine sFlt-1 compared with vehicle control. Furthermore, treating primary cytotrophoblasts with therapeutics which have been previously found to reduce sFlt-1 secretion, either reduced EGFR signaling (esomeprazole and statins) or perturbed mitochondrial function (esomeprazole, resveratrol, and metformin). Additionally, targeting both pathways simultaneously produced additive reductions in sFlt-1 secretion. Thus, we have identified 2 key survival pathways that seem to be overactive in preeclampsia and involved in the regulation of placental sFlt-1 secretion. Abstract : Supplemental Digital Content is available in the text.